2021
DOI: 10.3390/antiox10081300
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Melanoidin Pigment as a New Antioxidant Component of Fermented Willowherb Leaves (Epilobium angustifolium)

Abstract: Willowherb (Epilobium angustifolium L., family Onagraceae) is a well-known food and medicinal plant used after fermentation as a source of beverages with high antioxidant potential. Despite this long history of use, only a few papers have described the chemical profile and bioactivity of fermented willowherb tea in general. To understand the basic metabolic differences of non-fermented and fermented E. angustifolium leaves, we used general chemical analysis, high-performance liquid chromatography with photodio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 100 publications
1
9
0
Order By: Relevance
“…However, they noted that fermented red cabbage is still rich in anthocyanin content. Olennikov et al pointed that novel melanoidin is an essential antioxidant found in the fermented leaves of willowherb with a content of 145.31 ± 4.35 mg per gram dry plant weight, and it is worth further investigation as potential food and medical antioxidant [ 49 ].…”
Section: Impact Of Fermentation On Antioxidant Activity Of Various Plant-based Food Materialsmentioning
confidence: 99%
“…However, they noted that fermented red cabbage is still rich in anthocyanin content. Olennikov et al pointed that novel melanoidin is an essential antioxidant found in the fermented leaves of willowherb with a content of 145.31 ± 4.35 mg per gram dry plant weight, and it is worth further investigation as potential food and medical antioxidant [ 49 ].…”
Section: Impact Of Fermentation On Antioxidant Activity Of Various Plant-based Food Materialsmentioning
confidence: 99%
“…Similar teas are the most popular non-alcoholic beverages in the world due to the large number of health benefits [82,83]. Herbal teas, which are infusions and decoctions from leaves, roots, flowers, and plant seeds, are an important source of phenolic compounds in the human diet [84,85]. To assess the possible use of herbal tea from R. matsumuranus leaves, the phenolic compound content was analysed in infusions and decoctions obtained from extraction with water at different temperatures (Table 2).…”
Section: Stability Of R Matsumuranus Phenolic Compounds In Water Media: Comparison Of Infusion and Decoction Compositionmentioning
confidence: 99%
“…Alkaline hydrolysis of the polysaccharides was performed as previously described using 10% potassium hydroxide solution heating, 80% H 2 SO 4 neutralization, and liquid–liquid extraction with ethyl acetate [ 38 ]. Degradation products were analyzed by high-performance liquid chromatography with photodiode array detection and electrospray ionization triple quadrupole mass spectrometric detection (HPLC–PDA–ESI–tQMS) using an LC-20 Prominence liquid chromatograph coupled with an SPD-M30A photodiode array detector (wavelength range 200–600 nm), and an LCMS 8050 triple quadrupole mass spectrometer (Shimadzu, Columbia, MD, USA) with two-eluent gradient elution [ 39 ].…”
Section: Methodsmentioning
confidence: 99%